The "Second Sex" vs. The Forgotten Sex: - Wanis, Heba (AUC Knowledge Fountain, 2019)

(untitled)
This research explores the masculinity component of gender and development (GAD) interventions in Egypt. Women's empowerment has been the center of interventions in most developing countries, including Egypt. Men's engagement has been peripheral and limited to certain issues. The objective of this research was to gain insights about missing aspects regarding the involvement of men in developmental interventions, including suggestions for enhancing male engagement in communities. The research employed qualitative research methodology for data collection through focus groups with men in four villages in Assiut, and in-depth interviews with stakeholders of GAD. Analysis and coding of data was carried out using NVivo software using a pre-determined analysis framework that corresponded to content of data collection tools. Results revealed a diverse range of issues that men perceived to be needs, primarily economic empowerment and vocational training activities given the challenging economic conditions in Egypt. Other social issues, particularly marital relationships and parenting, were attributed to stressful economic conditions necessitating the need for psychosocial and psychoeducational interventions. This paper recommends placement of gender and masculinity interventions in the economic context of Egypt and a re-connection between gender policy and programming. There is a need for innovative participatory and asset-based programming by building on existing men's leadership in communities, while adapting successful interventions from other similar country contexts. This should be coupled with adopting a psychosocial and psychoeducational approach when targeting men. Sustainability (attaining community self-sufficiency) can be achieved through community capacity development and technical training of personnel implementing programs in communities.